The correlations between demographic factors, self-efficacy, and quality of life among Indonesian patients with ischemic stroke: A cross-sectional study - Azzahra, Nabila; Handayani, Fitria; Hidayati, Wahyu (Belitung Nursing Journal, 2025)
Background: Ischemic stroke is the primary cause of neurological disability and can lead to psychological issues that affect self-efficacy. Changes in self-efficacy, in turn, influence the overall quality of life. Although many studies have examined factors that affect self-efficacy, quality of life, or both, few have specifically explored the role of demographic factors in shaping the quality of life in patients with ischemic stroke. Objective: This study aimed to identify the correlations between demographic factors, self-efficacy, and quality of life Indonesian in patients with ischemic stroke. Methods: This study employed a quantitative approach with a cross-sectional design. A total of 143 participants were recruited between February and April 2024 based on defined inclusion criteria. The research instruments included a demographic questionnaire, the Stroke Self-Efficacy Questionnaire, and the Specific Stroke Quality of Life Questionnaire. Data were analyzed using descriptive statistics, logistic regression, and Spearman rank test. Results: The findings revealed that females were 2.213 times more likely (95% CI = 1.128–4.341; p = 0.031) to achieve high self-efficacy compared to males. Occupational status significantly influenced self-efficacy, with employed individuals being 6.333 times more likely (95% CI = 3.134–16.599; p <0.001) to achieve high self-efficacy. The duration of stroke experienced by respondents also had a significant impact, with an odds ratio (OR) of 1.908 (95% CI = 0.980–3.715; p = 0.025). Additionally, occupational status significantly affected the quality of life, as employed respondents were 7.213 times more likely to achieve a good quality of life (OR = 7.213; 95% CI = 3.134–16.599; p <0.001). There was a significant positive correlation between self-efficacy and quality of life (r = 0.898, p <0.001). Conclusion: The results of this study provide valuable insights for nursing practice, emphasizing the importance of interventions to enhance patients’ self-efficacy. By increasing patients’ confidence in managing their condition, such interventions can lead to improved quality of life and better recovery outcomes. Strategies including health education, psychological support, and patient empowerment during rehabilitation are essential for strengthening self-efficacy and improving overall care outcomes. These findings highlight the need for healthcare professionals and families to address the psychological aspects of care in patients with stroke. Enhancing self-efficacy is critical in helping patients achieve a better quality of life and more successful recovery.